Botticellis Triptychon der Verklärung Christi: Einblicke in seine geistig-geistliche Welt - Doetsch, Ingeborg Eugenia (Georg Olms Verlag, 2024)
This study focuses on the triptych of the 'Transfiguration of Christ' (c. 1500), a lesser-known late work by Sandro Botticelli. It reveals previously unrecognized, complexly coded symbols within the pictorial inventions in the triptych, which, among other things, present Christ appearing in his 'Transfiguration' as the archetype of God according to Genesis 1:26. The theme of androgyny, which is so significant for the history of religion, is experiencing a new topicality in our present day and was probably discussed in the circle of Marsilio Ficino, to which Botticelli belonged. The intellectual and spiritual prerequisites in the painter's personality play a key role in the interpretation of this late work.